2007
DOI: 10.1007/s00266-007-9022-9
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet-Rich Plasma as an Adipocyte In Vivo Delivery System: Case Report

Abstract: Tissue engineering has emerged as a promising alternative to current clinical treatments for restoration of soft tissue defects. A key element in the process of tissue engineering is an ideal implant that provides structural support and a favorable environment for growing cells. The authors hypothesized that autologous platelet-rich plasma (APRP) could be used as an in vivo adipocyte delivery system to favor cell survival and to stimulate early recruitment of microcapillaries to the site of implantation. Autol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…Application of autologous PRP has been reported to facilitate wound healing in several fields, including facilitating bone proliferation in orthopedic surgery, regenerating periodontal ligaments and accelerating the wound healing process in diabetic ulcers (2)(3)(4). Therefore, in this study, we applied autologous PRP not only to surgical wounds, but also to various forms of ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Application of autologous PRP has been reported to facilitate wound healing in several fields, including facilitating bone proliferation in orthopedic surgery, regenerating periodontal ligaments and accelerating the wound healing process in diabetic ulcers (2)(3)(4). Therefore, in this study, we applied autologous PRP not only to surgical wounds, but also to various forms of ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical applications PRP has been used to facilitate bone proliferation in nonunion fractures of joint replacement of orthopedic surgery, regeneration of periodontal ligaments, and to accelerate the wound healing process in diabetic ulcers (2)(3)(4). However, the precise molecular mechanisms of the PRP-induced wound healing process remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Princeton, New Jersey) to process 18 cc of peripheral blood. Recent studies have shown excellent results when autologous fat is combined with PRP in aesthetic plastic surgery (73,74,75). In order to increase the potential for autologous fat graft acceptance and retention we mix the harvested fat with the autologous PRP in a 4:1 ratio.…”
Section: Fat Preparationmentioning
confidence: 99%